Groundbreaking Ceremony for New Billinger Appliance Store - Jane Tolmach:::::: (1973)
An outline for a speech presented during a groundbreaking ceremony discussing the redevelopment of Oxnard and hoping that the Billinger Appliance Store has a bright future.